Renters Rising! Extending the analysis of housing activism in Europe to the UK - Mathers, Andrew (Araucaria, 2021)
The material effects of austerity in the UK have generated a resurgence of activist initiatives in the field of housing central to which is ACORN that has developed into a federated organisation contesting housing practices and policies at both local and national levels. ACORN is used to expand the examination of housing activism in Europe beyond the cases in Spain and Germany to the United Kingdom (Ordonez et al, 2015). This article also utilises the qualitative methodology of a comparative case study and the framework of ideological and social backgrounds, political repertoires and political logics to present and analyse ACORN. While ACORN displays striking similarities to other cases, it also represents a different trajectory in housing activism that combines direct action with an engagement with party politics as social democracy seeks to return to its roots.